Outcomes of vascular access in hemodialysis patients: Analysis based on the Korean National Health Insurance Database from 2008 to 2016 - Hyung Seok Lee; Young Rim Song; Jwa Kyung Kim; Narae Joo; Cheolsu Kim; Hyung Jik Kim; Sung Gyun Kim (The Korean Society of Nephrology, 2019)
Background : Controversies exist whether arteriovenous fistula (AVF) placement is preferred over arteriovenous graft (AVG) for elderly patients. Current guidelines did not offer specific recommendations. Thus, this study was conducted to analyze the all-cause mortality and primary patency associated with various vascular access (VA) types according to age group. Methods : This retrospective observational study investigated the Korean insurance claims data of chronic kidney disease patients who began hemodialysis between January 2008 and December 2016. We investigated all-cause mortality associated with initial VA in incident hemodialysis patients and primary patency between AVF and AVG according to age group. Results : The proportion of patients with a tunneled dialysis catheter (TDC) that was first placed for VA increased from 18.4% in 2008 to 52.3% in 2016. Incident hemodialysis patients with a TDC or AVG for the initial VA had significantly higher mortality risk than patients with an AVF, except for patients over 85 years, who showed no significant difference in all-cause mortality regardless of VA type. In the patency analysis on initial AV access, AVG had significantly poorer primary patency than AVF in all age groups. Conclusion : AVF had better patency than AVG in all age groups; however, the benefit of AVF attenuated in the older age groups. The mortality rate between AVF and AVG was not significantly different in patients over 85 years. Therefore, a "patient-first" approach should be emphasized over a "fistula-first" approach in AV access creation for incident hemodialysis patients older than 85 years.